Thriving in a Changing Academic Landscape: Moving at the Speed of Light - Brenda Sims; Christy Crutsinger (Academic Chairpersons Conference Proceedings, 2016)
Academic leaders are facing pressure to change how they deliver education. To respond, universities are increasingly charged with setting up educational programs that challenge the traditional notion of delivering classes. Using a case study approach, this session highlights how one university built a collaborative industry hub , developed interdisciplinary programs, and gained departmental and faculty buy-in in a sixth month window. Strategies for remaining nimble and transforming the ivory tower will discussed.
Keywords: Faculty; leadership; change; management; pressing issues